2005
DOI: 10.1111/j.1582-4934.2005.tb00344.x
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of peritubular capillaries C3d deposition in IgA glomerulonephritis

Abstract: The IgA glomerulonephritis (IgAGN) is one of the most common primary glomerulonephritis and has a variable and difficult to predict evolution toward the end‐stage nephrosclerosis. The deposition of C3d complement component in peritubular capillaries (PTCs) indicates a variant type of acute rejection while C3d deposition in primary glomerulonephritis (GN) is poorly documented. The aim of this study is to examine C3d expression in peritubular capillaries (PTCs) as a predictive marker and its correlation with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…Glomerular capillary C3d deposition may also serve as a new marker in the pathological diagnosis of MN at stage I, in patients who are treated with glucocorticoids. In recent years, various studies have explored the C3 deposition in glomerular capillaries and arterioles in association with IgAN and have revealed that peritubular capillary C3 deposition may be used as a predictor of a poor prognosis, while C3 deposition in the renal arterioles may be considered a marker of atherosclerosis [ 20 , 22 ]. In addition, C3 deposition in the glomerular capsule and/or arterioles is related to the clinical outcome of IgAN [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glomerular capillary C3d deposition may also serve as a new marker in the pathological diagnosis of MN at stage I, in patients who are treated with glucocorticoids. In recent years, various studies have explored the C3 deposition in glomerular capillaries and arterioles in association with IgAN and have revealed that peritubular capillary C3 deposition may be used as a predictor of a poor prognosis, while C3 deposition in the renal arterioles may be considered a marker of atherosclerosis [ 20 , 22 ]. In addition, C3 deposition in the glomerular capsule and/or arterioles is related to the clinical outcome of IgAN [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the serum levels of IgA are notably increased in 1/3 to 1/2 of the patients with IgAN (11–14). Although the serum C3 level tends to decrease in the active stage of CGN, it is generally considered that serum C3 level shows a normal range in patients with IgAN (15). Therefore, it is implied that the elevation of serum IgA level and serum IgA to C3 (IgA/C3) ratio are valuable indexes for predicting IgAN.…”
mentioning
confidence: 99%
“…IgAN (15). Therefore, it is implied that the elevation of serum IgA level and serum IgA to C3 (IgA/C3) ratio are valuable indexes for predicting IgAN.…”
mentioning
confidence: 99%
“…El depósito de C3 y C4, en las biopsias renales de NIgA, sugiere la activación de la vía alternativa y de las lectinas. Desde el punto de vista clínico, el depósito de C4d en el mesangio y C3d en células peritubulares se ha asociado a formas agresivas de la enfermedad 21,22 . Ya se han evaluado bloqueadores del complemento en pacientes con nefritis lúpica y vasculitis ANCA e incluso se reportó el uso de eculizumab en un paciente NIgA refractaria a esteroide, ciclofosfamida y plasmaféresis [23][24][25] .…”
Section: Revisión De La Literaturaunclassified